Study of TiAl thin films on piezoelectric CTGS substrates as an alternative metallization system for high-temperature SAW devices - Marietta Seifert (Journal of Materials Research and Technology, 2021)
Ti/Al multilayer films with a total thickness of 200 nm were deposited on the high-temperature (HT) stable piezoelectric Ca3TaGa3Si2O14 (CTGS) as well as on thermally oxidized Si (SiO2/Si) reference substrates. The Ti–Al films were characterized regarding their suitability as an alternative metallization for electrodes in HT surface acoustic wave devices. These films provide the advantage of significantly lower costs and in addition also a significantly lower density as compared to Pt, which allows a greater flexibility in device design. To realize a thermal stability of the films, AlNO cover as well as barrier layers at the interface to the substrate were applied. The samples were annealed for 10 h at up to 800 °C in high vacuum (HV) and at 600 °C in air and analyzed regarding the γ-TiAl phase formation, film morphology, and possible degradation. The Ti/Al films were prepared either by magnetron sputtering or by e-beam evaporation and the different behavior arising from the different deposition method was analyzed and discussed. For the evaporated Ti/Al films, AlNO barriers with a lower O content were used to evaluate the influence of the composition of the AlNO on the HT stability. The sputter-deposited Ti/Al films showed an improved γ-TiAl phase formation and HT stability (on SiO2/Si up to 800 °C in HV and 600 °C in air, on CTGS with a slight oxidation after annealing at 800 °C in HV) as compared to the evaporated samples, which were only stable up to 600 °C in HV and in air.